2020
DOI: 10.3390/met10101339
|View full text |Cite
|
Sign up to set email alerts
|

Production-Related Surface and Subsurface Properties and Fatigue Life of Hybrid Roller Bearing Components

Abstract: By combining different materials, for example, high-strength steel and unalloyed structural steel, hybrid components with specifically adapted properties to a certain application can be realized. The mechanical processing, required for production, influences the subsurface properties, which have a deep impact on the lifespan of solid components. However, the influence of machining-induced subsurface properties on the operating behavior of hybrid components with a material transition in axial direction has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Precision hard turning offers better fatigue life due to the low surface roughness, as well as the residual stress state, which is compressive and maximum at the subsurface depth. The residual stress distributions are of considerable importance; several investigations have reported that compressive residual stresses induced by the manufacturing process can extend the fatigue life of bearings up to 2.5 times [ 20 , 23 , 37 ]. Low surface roughness and subsurface residual stresses are the key parameters for extending bearing fatigue life.…”
Section: Resultsmentioning
confidence: 99%
“…Precision hard turning offers better fatigue life due to the low surface roughness, as well as the residual stress state, which is compressive and maximum at the subsurface depth. The residual stress distributions are of considerable importance; several investigations have reported that compressive residual stresses induced by the manufacturing process can extend the fatigue life of bearings up to 2.5 times [ 20 , 23 , 37 ]. Low surface roughness and subsurface residual stresses are the key parameters for extending bearing fatigue life.…”
Section: Resultsmentioning
confidence: 99%
“…Hard turning cycles have been widely used for many decades in the real industry for the production of critical components after quenching [ 1 ]. Hard turning can be employed for surface finishing [ 2 ] or in combination with grinding [ 3 ]. The surface state after hard turning is different as compared with hard turning [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing demands on components’ functionality has led to novel concepts for their manufacturing, together with the application of progressive materials [ 1 , 2 , 3 ]. The high tempered steels undergo the conventional quenching process when a component is rapidly cooled down from a high temperature, followed by tempering in the furnace at an elevated temperature.…”
Section: Introductionmentioning
confidence: 99%